2011
DOI: 10.1080/02589001.2011.603211
|View full text |Cite
|
Sign up to set email alerts
|

Tourism and the Eritrean Diaspora

Abstract: Eritrean Diasporictourism is a striking example of how Diasporas are not only victims of the nation state, but also play a great role in wider transnational cultural and economic dynamics of change. The present economic and political situation in Eritrea and the stability reached in Milan has diminished the probability that Eritreans in the Diaspora will return to Eritrea to live. Nevertheless, many people in this Diaspora community return to Eritrea for holidays at least every two years. The Eritrean summer r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The dimension labeled “escaping” generally reported the least mean score on the DTMS (grand mean = 3.80). Although an in-depth exploration of this motivation within the literature remains to be undertaken, Arnone (2011) submits that some diaspora tourists want to break off from routines in their society. This motivation, on the one hand, is more connected to leisure than diaspora tourism.…”
Section: Discussionmentioning
confidence: 99%
“…The dimension labeled “escaping” generally reported the least mean score on the DTMS (grand mean = 3.80). Although an in-depth exploration of this motivation within the literature remains to be undertaken, Arnone (2011) submits that some diaspora tourists want to break off from routines in their society. This motivation, on the one hand, is more connected to leisure than diaspora tourism.…”
Section: Discussionmentioning
confidence: 99%
“…Having naturalized in their country of asylum, and having fled a very different set of circumstances in pre-1991 Eritrea (i.e., the liberation conflict between Eritrea and Ethiopia as opposed to repression by the country's current ruling party), return does not threaten their residency or citizenship rights in their country of asylum. As such, these earlier generations of refugees and migrants visit Eritrea periodically, often to coincide with the country's patriotic holidays, to check in on businesses, or during their children's school holidays (Arnone, 2011). Among residents conscripted into the country's indefinite national service program, who are generally granted extremely limited personal liberties in all spheres of life, external citizens come to be seen as privileged citizens, a view that is only reinforced by national propaganda that praises them for their economic and political support to the nation Riggan (2013b).…”
Section: Stratified Citizenship and The History Of Return In Eritreamentioning
confidence: 99%
“…Many migrants, especially economic migrants and refugees, cannot or do not desire to travel back home; others return permanently one day (Long & Oxfeld, ). Yet others embark on temporary visits, essentially touristic journeys, for the purpose of visiting family and friends, but also a host of other reasons, including religion, education, health, recreation or economic activities (Feng & Page, ; Duval, ; Lew & Wong, ; Nguyen & King, ; Asiedu, ; Arnone, ). Overt pragmatic reasons may be underpinned by deeper psychological needs, such as emotional attachments to people and places; longings and cravings; the psychogoical power of nostalgic memories and remembered personal links; as well as issues of personhood and belonging associated with the ‘in‐betweenness’ of migrant identity.…”
Section: Diasporic Tourism and Transnational Migrant Home Visitsmentioning
confidence: 99%
“…However, as much as the encounter of the former home fosters fond memories and nostalgia, it may simultaneously reinforce a sense of belonging to the host country and even result in estrangement from one's roots, as migrants discover how much life in their old country has changed, or how much they themselves have changed (Tie, Holden, & yu Park, 2015). Arnone's () investigation of Eritrean migrants in Italy, one of the few examples of scholarship focussed on the African context, revealed that members of this diasporic population travel to their homeland specifically to perform touristic identities. They prefer to stay in hotels, rather than with family and engage in visiting heritage sites and tourist attractions to emphasize the contrast with their former lives and identities.…”
Section: Diasporic Tourism and Transnational Migrant Home Visitsmentioning
confidence: 99%
See 1 more Smart Citation